2018
DOI: 10.1007/s00392-018-1391-3
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation reduction by renal sympathetic denervation: 12 months’ results of the AFFORD study

Abstract: Aim The purpose of this pilot study was to assess whether renal sympathetic denervation (RDN) decreases atrial fibrillation (AF) burden in hypertensive patients with symptomatic AF at 6- and 12-month follow-up, as measured using an implantable cardiac monitor (ICM). Methods and results A total of 20 patients with symptomatic paroxysmal or persistent AF (EHRA ≥ II) and primary hypertension with a mean office systolic blood pressure (BP) of > 140 mmHg were enrolled. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…Recently, the AFFORD study, a single-arm pilot study including 20 patients with symptomatic paroxysmal or persistent AF, suggested that RDN alone was safe and able to decrease AF burden in min/day as measured using an implantable cardiac monitor (ICM) at 12-month follow-up accompanied by an improvement in quality of life (Feyz et al, 2018). A clinical study that assessed the antiarrhythmic effect of RDN in addition to pulmonary vein isolation (PVI) in HTN patients with symptomatic AF demonstrated that a mean BP reduction of 5–10 mmHg led to a 7% decrease in AF burden as measured with an ICM (Romanov et al, 2017).…”
Section: Renal Denervation and Ganglionated Plexi Ablationmentioning
confidence: 99%
“…Recently, the AFFORD study, a single-arm pilot study including 20 patients with symptomatic paroxysmal or persistent AF, suggested that RDN alone was safe and able to decrease AF burden in min/day as measured using an implantable cardiac monitor (ICM) at 12-month follow-up accompanied by an improvement in quality of life (Feyz et al, 2018). A clinical study that assessed the antiarrhythmic effect of RDN in addition to pulmonary vein isolation (PVI) in HTN patients with symptomatic AF demonstrated that a mean BP reduction of 5–10 mmHg led to a 7% decrease in AF burden as measured with an ICM (Romanov et al, 2017).…”
Section: Renal Denervation and Ganglionated Plexi Ablationmentioning
confidence: 99%
“…RDN has been though to reduce sympathetic overactivity and arrhythmogenic foci/substrate arising from it 12 . RDN alone without PVI has been shown to reduce AF burden and increase the quality of life in patients with AF 11 . Furthermore, RDN in PVI patients was shown to reduce left ventricular septal thickness and posterior wall thickness 13,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Renal denervation (RDN) may attenuate the hyperactive sympathetic nervous system which in turn leads to a reduction in RAAS activation and lowering of blood pressure 9,10 . RDN with or without PVI has been shown to reduce AF burden in hypertensive patients 11,12 …”
Section: Introductionmentioning
confidence: 99%
“…As a stand-alone therapy, RDN may also promote reverse-remodeling and improve atrial substrate. A pilot trial of 20 patients with paroxysmal or persistent AF and hypertension showed that RDN reduced AF burden and improved quality of life (54). Moreover, RDN reduced atrial conduction time, complex fractionated atrial activity, and ventricular mass in 14 patients with treatment-resistant hypertension (55).…”
Section: Atrial Fibrillationmentioning
confidence: 99%